'UNBOUNDED VIEWS': INCOMPLETE EKPHRASIS AND THE VISUAL IMAGINATION IN VIRGIL. (6th May 2016) - Kania, Raymond
Abstract : Our imagination loves to be filled with an object or to grasp at anything that is too big for its capacity. We are flung into a pleasing astonishment at such unbounded views and feel a delightful stillness and amazement of the soul at the apprehension of them. Joseph Addison, Essay 412